A GLUTARIMIDE FROM THE INDONESIAN MARINE CYANOBACTERIUM Oscillatoria sp. - Viqqi Kurnianda; . Khairunnisa; Sofyatuddin Karina; Sri Agustina; Nurfadillah Nurfadillah; Musri Musman (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2021)
In continuous concern of marine resources relating to molecular structures that have biological activity around the western part of the Indonesian Archipelago, a marine cyanobacterium species Oscillatoria sp. was found in Sabang Island, Aceh. This study aimed at investigating the chemical and biological contents of Oscillatoria sp. The isolation of the target molecule was carried out based on bioassay-guided separation with several steps of chromatography. In addition, the evaluation of bioactivity was determined by the MTT assay protocol against the human pancreatic cancer Panc-1 cell line. The planar structure of the target molecule was determined by spectroscopic analysis. Results showed that the whole planar structure was identified as cycloheximide-4-acetate (1), a cycloimide class of molecule. Moreover, the relative stereochemistry was confirmed by nuclear overhauser effect (NOE) analysis. Therefore, the molecule was assigned as (2S*,4S*,6S*,7R*)-cycloheximide-4-acetate. The cytotoxicity evaluation of compound 1 showed IC50 value of 0.32 mM against the human pancreatic cancer cell. Dalam perhatian berkelanjutan terhadap sumber daya laut yang berkaitan dengan struktur molekul yang memiliki aktivitas biologis di sekitar bagian barat Kepulauan Indonesia, spesies sianobakteria Oscillatoria sp. ditemukan di Pulau Sabang, Aceh. Penelitian ini bertujuan melakukan investigasi kandungan kimiawi dan biologis dari Oscillatoria sp. Isolasi molekul target dilakukan melalui metode pemisahan berdasarkan uji bioaktivitas dengan menggunakan beberapa tahapan kromatografi. Selain itu, evaluasi bioaktivitas ditentukan oleh protokol uji MTT terhadap sel kanker manusia Panc-1. Struktur planar dari molekul target ditentukan dengan analisis spektroskopi. Hasilnya, struktur planar dari senyawa target diidentifikasi sebagai sikloheksimida-4-asetat (1), kelompok molekul sikloimida. Selanjutnya, relatif stereokimia dikonfirmasi oleh analisis nuclear overhauser effect (NOE). Oleh karena itu, molekul tersebut ditetapkan sebagai (2S*,4S*,6S*,7R*)-sikloheksimida-4-asetat. Evaluasi sitotoksisitas pada senyawa 1 menunjukkan nilai IC50 sebesar 0.32 mM terhadap sel kanker pankreas.